Variability of cyclosporine concentrations by HPLC and TDX monoclonal assay methods, application of a correction factor, and description of a novel clinical approach to determine the practical consequences of changing assay technique. (29th October 2012) - Trifilio, Steven M.; Scheetz, Marc; Borensztajn, Jayme; Mehta, Jayesh
Abstract Cyclosporine (CSA) is an immunosuppressant used for the prevention of graft rejection and graft‐versus‐host disease (GVHD) during hematopoietic stem cell transplantation. Therapeutic drug monitoring (TDM) is recommended to ensure efficacy and prevent toxicity. Several immunoassay assay are commercially available for measuring CSA drug concentrations. Differences in the cross‐reactive metabolites measured by specific immunoassay tests contribute to the significant lack of specificity which has been reported between immunoassays and high performance liquid chromatography (HPLC) test results. Inter‐assay test results can affect interpretation of CSA drug concentrations and potentially compromise patient outcomes. The current study analyzed 72 paired HPLC‐monoclonal TDX (TDXm) CSA drug concentrations and calculated a clinically reliable correction factor which could be applied to HPLC‐TDXm results for TDM. A unique concordance–discordance simulation model was utilized to validate the correction factor for clinical use.